Índice de libertad económica en los países andinos: estudio de caso periodo 2018-2022. - Escudero Zapata, Airin Mallerly; Briceño Reyes, Joselyn Paulette (Machala : Universidad Técnica de Machala, 2024)
The research focused on determining the evolution of the Index of Economic Freedom in the Andean countries during the period 2018-2022, using a quantitative approach and an analytical-synthetic method with data provided by The Heritage Foundation. The results revealed that Bolivia was the least economically free economy, facing structural challenges, while Colombia led the index with moderate stability in 2018, 2020, and 2021. Peru maintained a moderately free position with solid indicators, and Ecuador experienced improvements in monetary and judicial freedom, although it faced challenges in other aspects. The main economic policies supporting economic freedom were fiscal policies and trade agreements. Additionally, institutional factors influenced the political structure of governments, with state interventions and corruption hindering growth in the nations. Despite variations in economic freedom and economic growth, negative correlation coefficients were detected that do not support the existence of a direct relationship. Therefore, it is important to note that the limited duration of the analyzed period, comprising only five years, influenced the ability to establish significant correlations between the research variables in these nations.
La investigación se centró en determinar la evolución del Índice de Libertad Económica de los países Andinos durante el período 2018-2022, utilizando un enfoque cuantitativo y un método analítico-sintético con datos proporcionados por The Heritage Foundation. Los resultados revelaron que Bolivia fue la economía menos libre, enfrentando desafíos estructurales, mientras que Colombia lideró en 2018, 2020 y 2021 el índice con estabilidad moderada. Perú mantuvo una posición moderadamente libre con sólidos indicadores y Ecuador experimentó mejoras en libertad monetaria y judicial, aunque enfrentó desafíos en otros aspectos. Las principales políticas económicas que apoyaron la libertad económica fueron las fiscales y los acuerdos comerciales. Además, los factores institucionales incidieron en la estructura política de los gobiernos, con intervenciones estatales y corrupción obstaculizando el crecimiento en las naciones. A pesar de las variaciones en la libertad económica y el crecimiento económico, se detectaron coeficientes de correlación negativos que no respaldan la existencia de una relación directa. Por lo tanto, es importante señalar que la limitada duración del período analizado, compuesto por solo cinco años, influyó en la capacidad de establecer correlaciones significativas entre las variables de investigación en estas naciones.
Keywords: INDICE DE LIBERTAD ECONOMICA; PAISES ANDINOS; CRECIMIENTO ECONOMICO